9 bottles of water can buy when cost of each bottle is $4. So, 36 bottles of water for $4 is better option.
Given that, Target sells 24 bottles of water for $3, and 36 bottles of water for $4.
The unitary method is a technique for solving a problem by first finding the value of a single unit, and then finding the necessary value by multiplying the single unit value.
Now, number of bottles of water = 24 ÷ 3 = 8
36 bottles of water for $4
Here, the number of bottles of water = 36 ÷ 4 =9
Therefore, 9 bottles of water can buy when cost of each bottle is $4. So, 36 bottles of water for $4 is better option.
To learn more about the unitary method visit:
brainly.com/question/22056199.
#SPJ5
3 arrays - 1 x 9 (or 9 x 1) and 3 x 3
Hence, the number of arrays = 2 x 2 = 4 = even
First, we pair the different factors of 9.
The different factors of 9 are:
(1, 9) and (3, 3)
For each pair, Mr. Deets can make 2 arrays.
So, the total number of arrays that Mr. Deets can make = 2 x 2 = 4 and hence the number of arrays is even.
Answer:
4 arrays,
Number of arrays is even.
Step-by-step explanation:
∵ The possible pairs of two numbers which give 9 after multiplication,
( 3, 3) and (9, 1),
So, the possible array would be,
3 × 3, 9 × 1
Note : 9 × 1 can also be written as 1 × 9,
According to the question,
For each pair of different factors, there are two arrays,
3 × 3 and 9 × 1 are two arrays with no same factor,
Hence, the total arrays = 2 × 2 = 4
Which is an even number.
Answer: 1 pound and 14 ounces
Step-by-step explanation:
...
2
−
3
+
6
d
2
c
−3+
d
6
start fraction, c, divided by, 2, end fraction, minus, 3, plus, start fraction, 6, divided by, d, end fraction when
c
=
14
c=14c, equals, 14 and
d
=
3
Answer:
The answer = 6
Step-by-step explanation:
Given expression:
To evaluate the given expression, when and
Solution:
We have:
Plugging in and in the given expression, to evaluate.
⇒
Evaluating:
⇒
⇒ 6(Answer)
Answer:
hmm 6
Step-by-step explanation:
Steps:
Group like terms:
8p - 3 + 9p + 6p + 2p - 6p - 3p - 9p-3
Add similar elements:
8p - 3 + 9p + 6p + 2p - 6p - 3p - 9p = 7p
=7p−3
Answer: =7p−3
Please mark brainliest
Hope this helps.
Answer:
7p-3
Step-by-step explanation:
We are given the expression:
8p - 3 + 9p + 6p + 2p - 6p - 3p - 9p
To simplify, we can combine like terms. Add all the terms with a variable, then add the terms without a variable.
(8p + 9p + 6p + 2p - 6p - 3p - 9p)+ -3
(25p -18p) -3
7p-3